Transition-metal free alkylarylation of acrylamides initiated by radical C–C bond cleavage of the tertiary cycloalkanols. Issue 32 (14th March 2016) - Guo, Li-Na; Deng, Zhi-Qiang; Wu, Yong; Hu, Jie
Abstract : An efficient Na2 S2 O8 -promoted radical cyclization reaction of acrylamides with the tertiary cycloalkanols has been developed. This one pot procedure involves a tandem C–C bond cleavage and two C–C bonds formation process. Abstract : An efficient Na2 S2 O8 -promoted radical cyclization reaction of acrylamides with the tertiary cycloalkanols has been developed. This one pot procedure involves a tandem C–C bond cleavage and two C–C bonds formation process. The key advantages of this protocol are its transition-metal free, its operational simplicity and its excellent functional group tolerance, thus allowing a facile access to oxindoles containing a carbonyl group.